Analysis And Design Of Enterprise Architecture Using Togaf Adm Framework In Project Divisions Of Pt. Inti (persero) - Dini Salsabila di Kusumah; Yuli Adam Prasetyo; Rahmat Mulyana (eProceedings of Engineering, 2016)
PT. INTI is a state-owned company which engaged in telecommunication infrastructure since 1974. But starting 2009, PT. INTI began to expand its business focus became not only the telecommunications infrastructure, but also engineering solutions and product development. all business focus will work well if there is support from all the main functions and support functions. One of its functions is a function of the project. The project function is a function that is responsible for the project were obtained from the client. PT. INTI is having plan to change their business focus back to manufacture business. therefore, project functions also need to add new business process in way to support business changes. Dashboard Project monitoring can be one of new activities to support manufacture business from project function. In order to carry those new business activity, need to have an application that support those activities. Enterprise Architecture method that use to analyze the baseline EA and design target EA is TOGAF ADM which contain 9 phases. In this research, phases that will implemented starting from preliminary phase until opportunity and solution phase. This research resulted in a target enterprise architecture design with new application recommendation named Sciforma Project Performance monitoring which use to monitor all project that still progressed by PT. INTI and a little change on Local Area Network (LAN) infrastructure. Then all enterprise architecture design will summarize to IT Roadmap which contain timeline to implement all new recommendation. Keywords: Enterprise Architecture, TOGAF ADM, Project Performance Management, Project Management